Environment of capital Dhaka : plants, wildlife, gardens, parks, open spaces, air, water, earthquake - Islam, Md. Anwarul, 1955-; Ahmed, Sharif Uddin; Asiatic Society of Bangladesh (Dhaka : Asiatic Society of Bangladesh, 2010)
Contributed articles.
At head of title: Celebration of 400 years of capital Dhaka.
Includes bibliographical references and index.
Keywords: Human ecology -- Bangladesh -- History; Bangladesh -- Environmental conditions -- History